PENGARUH REVISI ANGGARAN, PARTISIPASI ANGGARAN, TINGKAT KESULITAN, SERTA EVALUASI DAN UMPAN BALIK TERHADAP PENCAPAIAN YANG EFEKTIF - Zachari Abdallah; Maryanto Maryanto; Zesmi Kusmila (LPPM Universitas Bina Bangsa, 2024)
Government has an important role in serving the needs of the people. The role is to make plans or work systems in government more directed and efficient, especially local governments must be able to improve their performance. To evaluate and improve government performance, an index is used in which there are core dimensions that become the main indicators, namely public financial management, fiscal performance, service provision and investment climate. The purpose of this study is to determine and analyze the effect of budget revision, budget participation, budget difficulty level, evaluation and feedback on effective budget achievement simultaneously and the effect of budget revision, budget participation, budget difficulty level, evaluation and feedback on partial effective budget achievement. The methods used in this study are survey and interview methods through questionnaires with quantitative research approaches and primary data sources. Meanwhile, to analyze the data obtained, Multiple Correlation Coefficient Analysis is used, Multiple Linear Regression Analysis, Determination Coefficient Analysis, and Hypothesis Test using Significance Test (t Test and F Test). There is a significant effect of evaluation and feedback on effective budget achievement. Partially, the budget revision variable has a significant effect on the effective budget achievement of the Jambi language office, the budget participation variable does not have a significant effect on the effective budget achievement of the Jambi language office, the difficulty level variable does not affect the effective budget achievement of the Jambi language office, the Evaluation and Feedback variables have no effect on the effective budget achievement of the Jambi language office, That the implementation of the budget whose purpose is to find out the possibility of deviations in one unit towards responsible leaders and feedback is very important for budget implementers because it can be used to anticipate deviations that may occur in the future period